2015
DOI: 10.1111/are.12934
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of Streptococcosis associated withStreptococcus iniaein Siberian sturgeon (Acipenser baerii) in China

Abstract: Streptococcus iniae has emerged as an important fish pathogen over the past few decades causing high losses in aquaculture farms all over the world. At least 27 species of fish have been documented to be infected by S. iniae, including cultured and wild populations. In August and October 2013, a serious infectious disease characterized by body ulcer, internal organs haemorrhages and nodules showing on epicardium occurred on the Acipenser baerii farms in Ya'an country, China. Histological examination revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 27 publications
11
32
0
Order By: Relevance
“…Clinical signs characterized mainly by erratic swimming near the surface and arching of the back were similar to the clinical observations seen in both naturally and experimentally infected fish (Deng et al, ; Soto et al, ; Wang, Xu, Wang, Wang, & Cao, ). However, unlike previous cases, these signs were likely related to the epaxial muscle lesions, and not to neurological pathology (Soto et al, ), as no brain or spinal cord lesions were observed in the submitted fish in the current study.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Clinical signs characterized mainly by erratic swimming near the surface and arching of the back were similar to the clinical observations seen in both naturally and experimentally infected fish (Deng et al, ; Soto et al, ; Wang, Xu, Wang, Wang, & Cao, ). However, unlike previous cases, these signs were likely related to the epaxial muscle lesions, and not to neurological pathology (Soto et al, ), as no brain or spinal cord lesions were observed in the submitted fish in the current study.…”
Section: Discussionsupporting
confidence: 79%
“…Despite the unusual pathologic presentation of the cases, bacteriological tests, 16S rRNA and gyr B gene sequencing confirmed infection of the fish with S. iniae . These diagnostic cases highlight the emergence of streptococcosis in cultured sturgeon, adding to the initial reports from Asia and North America (Deng et al, ; Soto et al, ). These previous cases were associated with acute high mortalities of ~ 43% (Deng et al, ) in the farm and of 30% in a tank (Soto et al, ), respectively, similar to the mortality index observed in the second outbreak of this study, demonstrating the harmful potential of this agent for sturgeon.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations